The biomechanical design of a training aid for a backward handspring in gymnastics - Rosamond, E. L.; Yeadon, M. R. (Sports Engineering, 2009)
This study was carried out to design, construct and assess a training aid to assist in the learning of a backward handspring. A backward handspring is often the first backward dynamic skill gymnasts will learn and so its performance can be accompanied by anxiety. International high performance coaches were surveyed to establish the key coaching requirements of a backward handspring training aid. A video analysis of the skill was used to determine characteristic dimensions of the skill, and these were used in the design of the training aid. The aid was designed and manufactured in accordance with European Standards for safety. The device`s safety for use in supporting the backward handspring was confirmed through testing. The assessment of the training aid using 11 gymnasts showed that it permitted a safe dynamic performance; provided support; did not obstruct technically good performances; allowed progressive use by novices without additional coach support; and was adjustable for gymnasts of various size and ability. When assessed against other training aids, it was the only aid that fulfilled all of the key coaching requirements.